Thermoacoustic heat pumping direction alteration by variation of magnitude and phase difference of opposing acoustic waves. (25th May 2016) - Widyaparaga, A.; Hiromatsu, T.; Koshimizu, T.; Deendarlianto, D.; Kohno, M.; Takata, Y.
Highlights: A dual speaker thermoacoustic heat pump was constructed. The acoustic field was altered by varying the phase and magnitude of speaker output. Change in acoustic field was shown to affect heat pumping in the regenerator. Heat pumping direction along the regenerator was seen to change and reverse. The change of SWC and TWC significantly affected heat pumping. Abstract: Thermoacoustic refrigeration utilizes the temperature changes that occur due to pressure oscillations within a sound wave to transport heat from one point to another and achieve cooling. As such, it neither requires complicated machinery nor hazardous or environmentally harmful refrigerants. By altering the acoustic field, it is possible to also alter the direction of heat pumping allowing a single device to be capable of functioning as a heater or cooler without addition of complicated machinery. We have constructed a thermoacoustic heat pump employing dual opposing acoustic drivers or speakers connected by a resonator tube and a regenerator formed by layers of steel mesh positioned at the centre of the resonator to investigate the alteration of the acoustic field due to the interaction of opposing travelling waves. The acoustic field was manipulated by changing the phase difference and magnitude difference between the waves generated by the acoustic drivers. Experimental results show that the acoustic power flow on both sides of the regenerator was altered thus resulting in a change in heat pumping direction along the regenerator. In addition, it was also observed that the heat pumping was also influenced by the changes in the standing wave component (SWC) and the travelling wave component (TWC).